O sujeito professor no discurso de autoajuda - (:unkn) unknown (Universidade Federal de Goiás, 2013)
This research aims to analyze the discursive effects of identity processes, observed in Brilliant parents, fascinating teachers, from Augusto Cury, one of the representative authors of selfhelp literature in Brazil. We used as theoretical and methodological devices French Discourse Analysis postulates, from Michel Pecheux´s and Michel Foucault´s contributions. Specifically we focus in this research, the notions of speech, subject and production conditions from Pêcheux and of subject/power, power/knowledge, ways of subjectivity and disciplinary practices from Michel Foucault. As a methodological approach we propose the description of statements based on the proposal for the development of Foucault's archaeological method. With the theoretical-methodological support we´ve analyzed the book in order to identify the identity processes proposal of the teacher subject. We observed a discourse that takes place in certain production conditions. The enunciator subject determines the places occupied in the process of dialogue which are: the place of an enunciator who holds a scientific knowledgepsychological, that aims, through a disciplinary and pastoral power, to establish truth regimes on the subject/reader/teacher, and the reader subject, a place determined by the enunciator, as the subject of the lack, one that is lost and need guidance to act promptly in your profession. It is proposed to the teachers subjects certain disciplines that constitute ways of subjectivity, which aims to get the discursive subject in a discursive mash, in order to make it docile and useful. For this, the enunciator establishes interdiscursive relationships with the following discourses: scientific, religious, and with official discourses on education as Parameters National Curriculum (PNC), this interdiscursivity shown produce senses since an identification with what is being said as true until the intimidation, punishment for mistakes. We´ve noted that the proposal of constitution of the teacher subject in this self-help discursivity is of an individual, homogenized subject, that will revolutionize education, a kind of sweet superhero. It is a discoursivity which imposes certain disciplines and does not respect the singularities.
The subject teacher of speech of self-help
Keywords: Autoajuda; Análise do discurso; Constituição identitária; Professor; Self-help literature; Discourse analysis; Identity process; Teacher; LETRAS::LINGUA PORTUGUESA